A comprehensive quality function deployment model for improving academics of technical institutes. Issue 2 (April 2021) - Karanjekar, SB; Lakhe, RR; Deshpande, VS
Quality has always been an issue of utmost concern for every technical education institute. There have been a lot of theoretical studies conducted that presented various methods of measuring quality of higher and technical education institutes. This paper presents a quantitative method to measure service quality of technical education institutes focusing on its academic aspects and taking into account various stakeholders such as Students, Teaching staff and the Industry. The paper presents a step-by-step process of stakeholder requirement assessment, their translation to service features, key processes and finally to key activities which are the suggestions to the management to take proper decisions and actions. Three distinct House of Qualities of Service Planning, Process Planning and Activity Planning have been presented in the paper to present a comprehensive model, which can be applied practically across the technical institutes. Uniqueness of the paper is that these three stakeholders are considered together for planning the service quality of technical institutes.